Christabel Pankhurst fundamentalism and feminism in coalition - Larsen, Timothy, 1967- (Woodbridge, UK Boydell, 2002)
Includes bibliographical references and index.
See also article on Christabel pankhurst in Ian McDowell's series on "Great women in the Brethren Movement, publlished in Outreach magazine.
Keywords: Pankhurst, Christabel, -- Dame, -- 1880-1958.; Brethren movement -- History -- 20th century; Fundamentalism -- History -- 20th century; Feminism -- Religious aspects -- Christianity -- History -- 20th century